Interpreting the Past, Understanding the Present
X, 218 p.
Keywords: The British Sociological Association held a conference on the theme "Sociology and History". In 1964, E.H. Carr had called for an open frontier between the disciplines. This book examines the traffic across this frontier and in particular, what might be called the sociological uses of history.